2018
DOI: 10.1016/j.nmni.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and molecular detection of multidrug-resistant Mycobacterium tuberculosis among tuberculosis lymphadenitis cases in Addis Ababa, Ethiopia

Abstract: Multidrug-resistant tuberculosis (MDR-TB) has emerged as a major public health problem. Drug-resistance surveillance data show that 3.9% of new and 21% of previously treated TB cases were estimated to have had rifampicin/ multidrug-resistant tuberculosis (MDR/RR-TB) in 2015. This implies that the MDR-TB is increasing alarmingly. Hence, a better understanding of drug resistance mechanisms and genotypes associated with multidrug resistance in M. tuberculosis is crucial for improving diagnostic and therapeutic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 24 publications
(26 reference statements)
3
45
2
Order By: Relevance
“…The two RIF R isolates identified in this study contained the S531L mutation in the rpoB gene, which is the most frequently reported rpoB mutation in the Ethiopian strains, 23 , 28–30 indicating the possible transmission of strains with similar types of mutations in the community. However, mutations at other codons including H526D and D516V had also been reported among RIF R isolates.…”
Section: Discussionmentioning
confidence: 73%
“…The two RIF R isolates identified in this study contained the S531L mutation in the rpoB gene, which is the most frequently reported rpoB mutation in the Ethiopian strains, 23 , 28–30 indicating the possible transmission of strains with similar types of mutations in the community. However, mutations at other codons including H526D and D516V had also been reported among RIF R isolates.…”
Section: Discussionmentioning
confidence: 73%
“…Of the total of 28 articles reviewed, 14 articles were from Ethiopia [16, 26, 3748] two articles each from Zambia [49, 50], South Africa [51, 52] and Nigeria [53, 54]. One article each were identified from Burkina Faso [55], Uganda [56], Djibouti [57], Mozambique [58], Sudan [59], Tunisia [60], Tanzania [61], and Malawi [62].…”
Section: Resultsmentioning
confidence: 99%
“…The national TB programs, however, have focused on PTB because of transmissibility, and likewise, the majority of studies done in Ethiopia focused on PTB [9]. Some of the previously conducted studies in Ethiopia focused on the genotypic characterization of mycobacterium causing EPTB [8,[10][11][12] and other assessed diagnostic modalities accuracy and sensitivity for lymph nodes TB [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. A detailed characterization incorporating sociodemographic, clinical, laboratory, and radiological features of adult EPTB cases is lacking in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The documented presenting symptoms were swelling of the affected area, 66.8%(18), night sweating 33.3% (9), loss of appetite, 29.6%(8), weight loss, 25.9% (7), fever, 22.2%…”
mentioning
confidence: 99%